Dampak Kerja Jarak Jauh pada Produktivitas Karyawan : Strategi Manajemen Humas dalam Meningkatkan Pelayanan Publik di Era Pascapandemi - Rizda Nirmala Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study discusses the impact of remote work on employee engagement and productivity in the post-pandemic era, focusing on public relations management and public service. The aim of the research is to analyze how the implementation of remote work affects employee performance and to identify managerial strategies that can enhance their engagement. The method used is literature research, collecting data from various relevant sources. The findings indicate that while remote work can enhance productivity, challenges such as burnout and communication difficulties persist. The implications of this research provide guidance for organizations to develop more effective remote work models that support employee well-being and encourage the adoption of appropriate technologies to enhance engagement in the workplace.